No individual or combined effects of caffeine and beetroot-juice supplementation during submaximal or maximal running - Oskarsson, K.; McGawley, K. (Applied Physiology, Nutrition, and Metabolism, 2018)
Dietary supplements such as caffeine and beetroot juice are used by athletes in an attempt to optimize performance and therefore gain an advantage in competition. The aim of this study was to investigate the individual and combined effects of caffeine and beetroot-juice supplementation during submaximal and maximal treadmill running. Seven males (maximal oxygen uptake: 59.0 ± 2.9 mL/kg·min) and 2 females (maximal oxygen uptake: 53.1 ± 11.4 mL/kg·min) performed a preliminary trial followed by 4 experimental test sessions. Each test session consisted of two 5-min submaximal running bouts (at ~70% and 80% of maximal oxygen uptake) and a maximal 1-km time trial (TT) in a laboratory. Participants ingested 70 mL of concentrated beetroot juice containing either 7.3 mmol of nitrate (BR) or no nitrate (PBR) 2.5 h prior to each test session, then either caffeine (C) at 4.8 ± 0.4 (4.3-5.6) mg/kg of body mass or a caffeine placebo (PC) 45 min before each test session. The 4 test sessions (BR-C, BR-PC, PBR-C, and PBR-PC) were presented in a counterbalanced and double-blind manner. No significant differences were identified between the 4 interventions regarding relative oxygen uptake, running economy, respiratory exchange ratio, heart rate (HR), or rating of perceived exertion (RPE) at the 2 submaximal intensities (P > 0.05). Moreover, there were no significant differences in performance, maximum HR, peak blood lactate concentration, or RPE during the maximal TT when comparing the interventions (P > 0.05). In conclusion, no beneficial effects of supplementing with typical doses of caffeine, beetroot juice, or a combination of the two were observed for physiological, perceptual, or performance responses during submaximal or maximal treadmill running exercise.